Genomes of the Venus Flytrap and Close Relatives Unveil the Roots of Plant Carnivory - Palfalvi, Gergo; Hackl, Thomas; Terhoeven, Niklas; Shibata, Tomoko F; Nishiyama, Tomoaki; Ankenbrand, Markus; Becker, Dirk; Förster, Frank; Freund, Matthias; Iosip, Anda; Kreuzer, Ines; Saul, Franziska; et al. (Current biology, 2020)
Most plants grow and develop by taking up nutrients from the soil while continuously under threat from foraging animals. Carnivorous plants have turned the tables by capturing and consuming nutrient-rich animal prey, enabling them to thrive in nutrient-poor soil. To better understand the evolution of botanical carnivory, we compared the draft genome of the Venus flytrap (Dionaea muscipula) with that of its aquatic sister, the waterwheel plant Aldrovanda vesiculosa, and the sundew Drosera spatulata. We identified an early whole-genome duplication in the family as source for carnivory-associated genes. Recruitment of genes to the trap from the root especially was a major mechanism in the evolution of carnivory, supported by family-specific duplications. Still, these genomes belong to the gene poorest land plants sequenced thus far, suggesting reduction of selective pressure on different processes, including non-carnivorous nutrient acquisition. Our results show how non-carnivorous plants evolved into the most skillful green hunters on the planet.
Keywords: WRKY transcription factors; gene loss; neofunctionalization; jasmonate signaling; transposon classification; tissue-specific genes; masožravé rostliny; biologická evoluce; genom rostlinný; Genome, Plant; whole-genome duplications; Biological Evolution; Carnivorous Plant; Droseraceae